To vaccinate or not to vaccinate? Experiences of COVID-19 vaccine uptake among people living with non-communicable diseases in Ghana: A qualitative study. - Leonard Baatiema; Leonard Baatiema; Sheba M P Kunfah; Olutobi A Sanuade; Luke N Allen; Seye Abimbola; Ama de-Graft Aikins; Kwadwo A Koram; Margaret E Kruk (PLOS Global Public Health, 2024)
Following the development of a vaccine for COVID-19, the expectation was instantaneous widespread distribution and uptake to halt further spread, severe illness and deaths from the virus. However, studies show very low uptake, especially in resource-poor settings, and little is documented about the drivers of vaccine uptake in populations classified as high-risk. In this study, we explored access and uptake of COVID-19 vaccines among people living with non-communicable diseases (PLWNCDs) in Ghana. A qualitative study using in-depth interviews and focus group discussions was conducted among adults (>18 years) PLWNCDs stratified by sex, age, and type of non-communicable diseases (NCDs) at the community level (non-users of the health service) and health facility levels. Purposive sampling was used to select eligible participants. Topic guides were used to facilitate the face-to-face in-depth interviews and focus group discussions. The interviews and discussions were all digitally audio recorded. All transcripts and field notes were thematically analysed. Overall, 62 participants were recruited for this study. Family members, friends/peers, health workers and media were identified as the main sources of information for COVID-19 vaccines. Several barriers that mediated access to the COVID-19 vaccines in Ghana were reported including mistrust of vaccine efficacy and fears of vaccine side-effects, long distance to and waiting hours at vaccination centres, shortages of vaccines at vaccination centres and non-prioritization of NCD patients for the vaccine. To improve uptake, intensified education and sensitization, house-to-house vaccination, expansion of vaccination centers and increased supply of vaccines were recommended by participants. Compared to studies elsewhere, misinformation and disinformation were not major causes of vaccine hesitancy. If policymakers can improve community-based vaccine delivery, reduce queues and waiting times, prioritize PLWNCDs and other vulnerable groups, and improve sensitization and communication-our findings suggest there will be major improvements in COVID-19 vaccine coverage in Ghana.